Trail Communication Regulated by Two Trail Pheromone Components in the Fungus-Growing Termite Odontotermes formosanus (Shiraki) - Wen, Ping (Public Library of Science, 2014)
The eusocial termites are well accomplished in chemical communication, but how they achieve the communication using trace amount of no more than two pheromone components is mostly unknown. In this study, the foraging process and trail pheromones of the fungus-growing termite Odontotermes formosanus (Shiraki) were systematically studied and monitored in real-time using a combination of techniques, including video analysis, solid-phase microextraction, gas chromatography coupled with either mass spectrometry or an electroantennographic detector, and bioassays. The trail pheromone components in foraging workers were (3Z)-dodec-3-en-1-ol and (3Z,6Z)-dodeca-3,6-dien-1-ol secreted by their sternal glands. Interestingly, ratio of the two components changed according to the behaviors that the termites were displaying. This situation only occurs in termites whereas ratios of pheromone components are fixed and species-specific for other insect cuticular glands. Moreover, in bioassays, the active thresholds of the two components ranged from 1 fg/cm to 10 pg/cm according to the behavioral contexts or the pheromonal exposure of tested workers. The two components did not act in synergy. (3Z)-Dodec-3-en-1-ol induced orientation behavior of termites that explore their environment, whereas (3Z,6Z)-dodeca-3,6-dien-1-ol had both an orientation effect and a recruitment effect when food was discovered. The trail pheromone of O. formosanus was regulated both quantitatively by the increasing number of workers involved in the early phases of foraging process, and qualitatively by the change in ratio of the two pheromone components on sternal glandular cuticle in the food-collecting workers. In bioassays, the responses of workers to the pheromone were also affected by the variation in pheromone concentration and component ratio in the microenvironment. Thus, this termite could exchange more information with nestmates using the traces of the two trail pheromone components that can be easily regulated within a limited microenvironment formed by the tunnels or chambers.